PROFILES OF COMPOUNDS IN ROOT EXUDATES OF RICE, CYMBOPOGON, DESMODIUM, MUCUNA AND MAIZE. - Godfrey, Kaiira Moses (Journal of Agricultural Sciences (Belgrade), 2019)
Roots of many crop species produce exudates with biologically active chemicals which are known to affect the growth of crops and weed species. An experiment was conducted at the Uganda National Crop Resources Research Institute, Namulonge, to identify compounds released in root exudates into soils potted with Cymbopogon nardus, Desmodium uncinatum, Oryza sativa, (NERICA 1), Mucuna pruriens and Zea mays (LONGE 6H) at fourty five days after planting. Organic compounds in soils were extracted using solid phase micro-extraction (SPME) and by solvent extraction. Samples were subjected to analysis using a 7890A Gas Chromatography system. Data files were transferred into a distinct folder and data was uploaded onto XCMS online platform for pair wise comparison and other related statistical analysis in the National institute of Science and Technology library. The blank soil produced 15 terpenoids, two alcohols and one each of trihalomethanes, ethers, phenols, ketones, furans, alkanes and aldehydes. Cymbopogon exuded five terpenoids, one phenol and an alkane. Desmodium plant roots released three terpenoids, one alkane and a phenol. Rice crop produced eight terpenoids, two alkanes and a furan. Five terpenoids, one phenol and an alkane were released by mucuna crop, while six terpenoids were found in maize root exudates. The profiled compounds from cymbopogon, desmodium, rice, mucuna and maize could be responsible for the allelopathic properties expressed by the study crops in natural and agricultural ecosystems, hence, the potential for synthesis and development of herbicides.
Keywords: alkanes; cymbopogon; desmodium; exudates; phenols; rice; terpenoids; Terpenoids; Alkanes; Cymbopogon; Desmodium; Exudattrs; Phenols; Rice